Online monitoring techniques for studying evolution of physical, rheological and chemical effects along the extruder - Covas, J. A. (2004)
During extrusion and/or compounding, polymeric systems may be subjected to a complex thermo-mechanical-chemical environment, therefore monitoring the evolution of physical, rheological and chemical effects along the extruder is an important tool assisting process understanding and optimisation. Online monitoring concepts that allow sample collection, rheology measurements and RTD characterisation at specific locations along the screw axis of an extruder are presented. Each practical set-up is presented, its operation is described and the results obtained are validated experimentally. Finally, examples of the use of the tools developed for the study of specific polymer systems are presented and discussed.